2016
DOI: 10.1002/jtr.2074
|View full text |Cite
|
Sign up to set email alerts
|

Non‐participation of Domestic Tourism: Analyzing the Influence of Discouraging Factors

Abstract: This study analyzes the factors that discourage non-tourists' participation in domestic tourism. Data were collected in 15 cities in China and analyzed using a comparative analysis and non-parametric ridit analysis. The findings indicate that (i) non-tourists have low internal travel motivation and attitude and are more likely to be under 25 or above 55 years old, less educated, less healthy, with small child(ren) and lower income; (ii) non-tourists consider less on destination environment and attraction, but … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 50 publications
2
13
0
Order By: Relevance
“…In addition, studies have often focused on Chinese tourists as an outbound tourist to international destinations [6,13] as opposed to domestic travellers. Furthermore, domestic tourism in China is a major contribution to tourist arrivals, revenues and traffic than the international market [17,18], presenting the domestic traveller as a valuable consumer. Based on the literature, there is a present gap in better understanding Chinese domestic tourist behaviour [18,19], especially in the context of food tourism [16].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, studies have often focused on Chinese tourists as an outbound tourist to international destinations [6,13] as opposed to domestic travellers. Furthermore, domestic tourism in China is a major contribution to tourist arrivals, revenues and traffic than the international market [17,18], presenting the domestic traveller as a valuable consumer. Based on the literature, there is a present gap in better understanding Chinese domestic tourist behaviour [18,19], especially in the context of food tourism [16].…”
Section: Introductionmentioning
confidence: 99%
“…Destination awareness, destination preference, intention to visit is the most common elements to be considered in analysing destination selection. These are influenced by such factors as personal characteristics, motives, values, attitudes, money, time, weather transportation, travel companion and others (Li, Meng, Zhang, 2016). It can be concluded that there is a need to create interest to engage in domestic travel and that can be done by creating favourable conditions and rising awareness of travel, as observed previously in examples from cases in Russia (Veselova, 2017), Italy (Patuelli-, et.al., 2013) and India (Nair, Ramachandran, 2016).…”
Section: The Importance Of Domestic Tourismmentioning
confidence: 55%
“…Domestic tourism has largely remained an understudied research area (Barbhuiya and Chatterjee, 2020; Canavan, 2013; Li et al, 2016; Tsui, 2017). Developing countries have generally perceived domestic tourism as a less profitable sector than international tourism (Morupisi and Mokgalo, 2017; Stone and Nyaupane, 2019).…”
Section: Introductionmentioning
confidence: 99%